Appraisal and repair of building structures introductory guide - Holland, R.; Montgomery-Smith, B. E.; Moore, J. F. A. (Thomas Telford, 1992)
Part of a series of concise guides for engineers on site, who are planning an investigation or are confronted with a problem. This guide covers general principles, methods and equipment, as well as legal and professional aspects and the preparation of reports.
Keywords: Building inspection.; Buildings -- Repair and reconstruction.; elektronické knihy; electronic books